Wind Flow Analysis on Software-Based U-Type Savonius Wind Turbine Blades Using Solidworks Flow Simulation - Muhammad Aulia; Randi Purnama Putra; Andre Kurniawan; Fitrah Qalbina (Unversitas Negeri Padang, 2026)
Savonius wind turbines are a type of vertical axis wind turbines that work based on the principle of drag force. The way this turbine works begins with a gust of wind that hits the turbine blades which are generally semi-cylindrical or resemble the letter